2011
DOI: 10.1007/s00432-011-1028-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies and prognostic factors of patients with primary germ cell tumors in the mediastinum

Abstract: ObjectiveThe aim of this study was to evaluate the clinical characteristics and survival outcomes of patients with primary mediastinal germ cell tumor (PMGCT) by identifying the prognostic factors and efficacies of different treatment modalities.MethodsFifty-five patients with PMGCT who were treated consecutively at Cancer Center, Sun Yat-sen University, Guangzhou, from 1988 to 2010 were evaluated retrospectively.ResultsFifty-two men and 3 women with a median age of 25 years were identified, of whom 17 (30.9%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 23 publications
(30 reference statements)
1
36
0
1
Order By: Relevance
“…Considering that single cisplatin-based chemotherapy is incapable of eliminating the residual tumor or micrometastases due to the extensive properties of germ cell tumors in the mediastinum (21), we added radiotherapy at the basic level of cisplatin-based regimens and noted a striking reduction in size of the tumor at the end of irradiation. At last, the curative effect of the present patient is remarkable, and the prognosis is favourable, which was in accord with previous reports (21,23,24).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Considering that single cisplatin-based chemotherapy is incapable of eliminating the residual tumor or micrometastases due to the extensive properties of germ cell tumors in the mediastinum (21), we added radiotherapy at the basic level of cisplatin-based regimens and noted a striking reduction in size of the tumor at the end of irradiation. At last, the curative effect of the present patient is remarkable, and the prognosis is favourable, which was in accord with previous reports (21,23,24).…”
Section: Discussionsupporting
confidence: 81%
“…Patients who received two treatments of chemotherapy plus surgery or radiotherapy had the longest survival time of 118.3 months compared with the median overall survival time of 87.9 months (p=0.000). They recommended that chemotherapy combined with a local therapy such as surgery or radiotherapy is a reasonable treatment strategy (21). It was reported that cisplatin-based chemotherapy is curative for the vast majority of patients with mediastinal seminoma (22).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, seminomas and nonseminomatous malignant germ cell tumours are generally treated with chemotherapy before surgery. 9,10 Thymic epithelial tumours are usually treated with surgery even if they have invaded surrounding structures and have pleural disseminations. 11 Therefore, the differential diagnosis of anterior mediastinal solid tumours has a clinical impact for physicians.…”
Section: Introductionmentioning
confidence: 99%
“…The chemotherapeutic effect varies between men with primary mediastinal seminoma (9). Another explanation is that the patient was diagnosed with mediastinal seminoma through biopsy.…”
Section: Discussionmentioning
confidence: 99%